THE AUTHORITY OF THE VILLAGE CHAIRMAN IN DRAFTING VILLAGE REGULATIONS - Wahyudi, Teguh Fidiah; Izomiddin, Izomiddin; Budianto, Kun (Nurani, 2021)
The issuance of.The Constitution Number6 2014 concerning Villages, hereinafter referred to as the Village Law, becomes a starting point for the village's hopes to be able to determine its position, role and authority over itself. The hope is that the village can be socially powerful and politically sovereign as the foundation of village democracy, as well as being economically empowered and culturally dignified as the face of village independence and village development. This hope is even more exciting when the combination of recognition and subsidiarity principles appears as the main principle that becomes the spirit of this law. Village Law Number 6 of 2014 concerning Villages supported by PP. 43 of 2014 concerning Implementation Regulations of Law Number 6 of 2014 concerning Villages, discusses the process of making Village regulations which are also regulated in the Minister of Home Affairs Regulation No. 111 of 2014, the formulation of the research problem wanted to know the process of making Village regulations according to The Constitution Number6 2014 concerning Village, the fund wants to know the authority of the village head in drafting village regulations in Ulak Pandan Village and Tanjung Pinang Village, Kecamata. West Merapi, Lahat Regency. based on The Constitution Number6 2014concerning Village, the theory used is the theory of coordination from Inu Dating, the methodology used in this research is descriptive analysis or qualitative research design with a case study model. In conducting this research the author uses a type of field research (Field Research), the result of this research is that the process of drafting village regulations in Ulak Pandan Village and Tanjung Pinang Village, District West Merapi, Lahat Regency is in accordance with The Constitution Number6 2014 on Villages which is supported by PP No. 43 of 2014 and Minister of Home Affairs Regulation No. 111 of 2014, drafting village regulations.